Monte Mozinho : a recuperação do sector B - Soeiro, Teresa (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
In this paper we aim at reporting the archeological campaigns that took place in the castro of Monte Mozinho, Penafiel, in the years from 1995 to 1997. They were centered in already digged areas of B sector, externai to the first wall, N and NE, alongside the road that is the back-bone of the village, showing occuparions from the l and III/IV th centuries D.C. Down the slopes of the settlement, outside the ramparts and beyond the necropolis, as found in other castro sites, a different kind of construction emerged, to be studied in detail in future excavations.